A Retrospective Review of 25 cases of Lethal Fetal Anomalies - FA, Dalia; I, Hamizah; N, Zalina; SL, Yong; A, Mokhtar (IIUM Medical Journal Malaysia, 2016)
Introduction: To review the gestational age at diagnosis, method of diagnosis, pregnancy outcome and maternal complications of prenatally diagnosed lethal foetal anomalies. Methods: Retrospective review of 25 women who had aborted or delivered foetuses with lethal anomalies in a tertiary hospital in 2011 based on patient medical records. Results: There were a total of 10,088 deliveries, in which 25 (0.24%) women were found to have conceived foetuses with lethal anomalies. All of them were diagnosed by prenatal ultrasound and only 7 (28.0%) had both prenatal ultrasound and genetic study done. The women’s mean age was 29.9 years old. The mean gestational age at diagnosis of lethal foetal anomalies was 25.5 weeks (SD=12.5) and mean gestational age at termination of pregnancy (TOP) or delivery was 28.5 weeks (SD=12.5). Seven (28%) women had early counseling and TOP at the gestation of < 22 weeks. Beyond 22 weeks of gestation, eight (32%) women had TOP and ten (40%) women had spontaneous delivery. Twenty (80%) women delivered or aborted vaginally, three (12%) women with assisted breech delivery and two (8%) women with abdominal delivery which were performed due to transverse foetal lie in labour and a failed induction, leading to emergency hysterotomy complicated by hysterectomy due to intraoperative finding of ruptured uterus. Overall, the associated post-partum adverse events included post-partum haemorrhage (12%), retained placenta (12%), blood transfusion (8%), uterine rupture (4%) and endometritis (4%). Mean duration of hospital stay was 6.6 days (SD 3.7 days). Conclusion: Late diagnosis of lethal foetal anomalies leads to various maternal morbidities, in this case series , which could have been prevented if they were diagnosed and terminated at early trimester. A new direction is needed in our local practice.